PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP PEMBELAJARAN MENULIS TEKS BERITA SISWA KELAS VII FASE D SMPN 33 PADANGPENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP PEMBELAJARAN MENULIS TEKS BERITA SISWA KELAS VII FASE D SMPN 33 PADANG - Silvina syaftarini; Yulia Sri hartati; Ria Satini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the effect of applying the Discovery Learning model on students’ news writing skills in Grade VII Phase D at SMP Negeri 33 Padang. The problem addressed was students’ limited creativity and difficulties in understanding news structure, mastering the 5W+1H elements, and presenting information clearly and coherently. A quantitative approach with a one group pretest-posttest experimental design was employed. The sample consisted of class VII.5 students selected through purposive sampling, and data were obtained from writing performance tests administered before and after the treatment. The results indicate a significant improvement in students’ writing skills after using the Discovery Learning model. The average pretest score was 64.44 (fair), which increased to 81.11 (good) in the posttest. Enhancements were observed in all aspects of news writing, including titles, leads, body, and conclusions. Statistical analysis confirmed that tcount exceeded ttable at a 95% significance level, proving the positive impact of Discovery Learning on students’ writing performance. In conclusion, this model effectively fosters active participation, creativity, and the ability to structure news information systematically and communicatively.